Gridded fossil CO2 emissions and related O2 combustion consistent with national inventories 1959–2018 - Matthew W. Jones (Nature Portfolio, 2021)
Measurement(s) carbon dioxide emission • oxygen combustion Technology Type(s) digital curation • computational modeling technique Factor Type(s) annual and monthly fossil carbon dioxide emissions estimates • annual and monthly oxygen combustion estimates Sample Characteristic - Environment climate system Sample Characteristic - Location global Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13333643